Role of Fine Needle Aspiration Cytology in the Diagnosis Of Pleomorphic Adenoma With Histological Correlation (Journal of Chittagong Medical College Teachers' Association, 2019)
Background: Fine Needle Aspiration Cytology (FNAC) has been widely accepted as an accurate and minimally invasive diagnostic procedure in the investigations of salivary gland masses. The aim of this study was to determine the accuracy of FNAC in the diagnosis of pleomorphic adenoma. Materials and methods: A cross sectional comparative study was carried out on a total of 28 patients with salivary gland swellings who underwent preoperative FNA examination. After surgical excision of tumours, all FNAC findings were subsequently verified with histopathological examination. All the necessary and relevant data were recorded methodically and meticulously and statistical analysis was done by computer software device (SPSS-18 version). Results: On preoperative FNA examination, among the 28 cases, 19 (67.9%) cases were pleomorphic adenomas. On histopathological examination, out of 28 cases, 20 (71.4%) cases were pleomorphic adenomas. Out of 19 cases of pleomorphic adenomas diagnosed by cytology, 17 cases were confirmed by histopathology. Remaining two cases revealed different diagnosis. In three cases of pleomorphic adenomas diagnosed by histopathology, the cytology revealed different diagnosis. In six cases of tumours other than pleomorphic adenoma there was agreement between cytological and histological diagnosis. The diagnostic sensitivity, specificity and accuracy of preoperative FNAC of pleomor phic adenoma were 85%, 75% and 82.1% respectively. The Positive Predictive Value (PPV) and Negative Predictive Value (NPV) of FNAC were 89.5% and 66.7% respectively. Conclusion: Fine needle aspiration cytology is a useful preoperative diagnostic tool in evaluating Pleomorphic adenoma of salivary gland.JCMCTA 2019 ; 30 (1) : 56-60